VEGETATION DIVERSITY AND INTENSITY OF PLANT PESTS AND DISEASES IN TWO POLYCULTURE SYSTEMS IN TANGGAMUS DISTRICT - ., Sudiono; Sutjahyo, Surjono Hadi; Wijayanto, Nurheni; Hidayat, Purnama; Kurniawan, Rachman (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Vegetation diversity and intensity of plant pests and diseases in two polyculture systems in Tanggamus District. The vegetable crop management cannot be separated from infestation of plant pest and disease which influences the quality and quantity of crop yield. The pest organism development is influenced by agroecosystem. The objective of this research was to analyze vegetation diversity and intensity of pest and disease in Tanggamus District. Methods used in this research were analysis of vegetation diversity based on Shannon index, percentage of pests damage and diseases incidence. The results showed that the vegetation diversity in polyculture of agriculture typology were 11 plant species with diversity index of 0.64; while in polyculture of agroforestry typology there were 11 plant species with diversity index of 0.74 and both of these indices were less than 1 (H? < 1). The percentage of pests damage in the polyculture of agriculture larger than polyculture of agroforestry typology ranging from 7.20% to 81.67% and 3.04% to 26.67% respectively. While the incidence of disease in polyculture of agriculture ranging from 0.65% up to 100% and polyculture of agroforestry typology 0.65% up to 68.00%.